PREDATOR-PREY RELATIONSHIP (CERVIDAE & CARNIVORA) AND ITS IMPACT ON FOSSIL PRESERVATION FROM THE SIWALIKS OF PAKISTAN - A. Ghaffar; M. A. Khan; M. Akhtar (Journal of Animal and Plant Sciences, 2009)
This paper deals with an introduction of new method that is a predator- prey relationship for preservation of fossils. For this purpose fossil record of order Carnivora and family Cervidae (order Artiodactyla) from late Miocene-Pleistocene times were studied. Our findings extend the idea that the predator-prey relationship is also an additional source for the preservation of fossils being preyed by predators. This test method is applied for the collected fossil material (carnivores and cervids), available at Abu Bakr Fossil Display and Research Centre, Department of Zoology, University of the Punjab, Lahore.
Keywords: Predator-prey relationship; Family Cervidae; Order Carnivora; Fossils